Clinical characteristics of coronavirus disease 2019 (COVID-19) in China: A systematic review and meta-analysis. Issue 6 (June 2020) - Fu, Leiwen; Wang, Bingyi; Yuan, Tanwei; Chen, Xiaoting; Ao, Yunlong; Fitzpatrick, Thomas; Li, Peiyang; Zhou, Yiguo; Lin, Yi-fan; Duan, Qibin; Luo, Ganfeng; Fan, Song; et al.
Summary: Objective: To better inform efforts to treat and control the current outbreak with a comprehensive characterization of COVID-19. Methods: We searched PubMed, EMBASE, Web of Science, and CNKI (Chinese Database) for studies published as of March 2, 2020, and we searched references of identified articles. Studies were reviewed for methodological quality. A random-effects model was used to pool results. Heterogeneity was assessed using I 2 . Publication bias was assessed using Egger's test. Results: 43 studies involving 3600 patients were included. Among COVID-19 patients, fever (83.3% [95% CI 78.4–87.7]), cough (60.3% [54.2–66.3]), and fatigue (38.0% [29.8–46.5]) were the most common clinical symptoms. The most common laboratory abnormalities were elevated C-reactive protein (68.6% [58.2–78.2]), decreased lymphocyte count (57.4% [44.8–69.5]) and increased lactate dehydrogenase (51.6% [31.4–71.6]). Ground-glass opacities (80.0% [67.3–90.4]) and bilateral pneumonia (73.2% [63.4–82.1]) were the most frequently reported findings on computed tomography. The overall estimated proportion of severe cases and case-fatality rate (CFR) was 25.6% (17.4–34.9) and 3.6% (1.1–7.2), respectively. CFR and laboratory abnormalities were higher in severe cases, patients from Wuhan, and older patients, but CFR did not differ by gender. Conclusions: The majority of COVID-19 cases are symptomatic with a moderate CFR. Patients living in Wuhan, older patients, and those with medical comorbidities tend to have more severe clinical symptoms and higher CFR.